2021
DOI: 10.1038/s41598-021-84658-z
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT in therapy control of infective native aortic aneurysms

Abstract: Infective native aortic aneurysms (INAA) are aneurysms arising from infection of the aortic wall. Treatment is demanding with 5-year survival rates between 53 and 55%. The aim of our study was to evaluate the usefulness of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) in the long-term monitoring of patients with proven INAA. Fifty-three PET/CT were performed in 15 patients with INAA in this single-center retrospective cohort study and retrospective analysis of prospectively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Along with previous results, the time-to-infection did not influence basic uptake values; however, the type of initial operation (EVAR vs. OAR) might ( Table 2 ) [ 7 , 22 ]. Similar results have been reported from smaller cohort studies and meta-analyses and also after open ascending aortic repair [ 23 , 24 , 25 , 26 , 27 , 28 ]. Yet, quantitative PET analysis could be suggestive of perigraft gas bubbles, but no correlations with eventual bacteria and clinical outcomes of VGEI are reported [ 6 , 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…Along with previous results, the time-to-infection did not influence basic uptake values; however, the type of initial operation (EVAR vs. OAR) might ( Table 2 ) [ 7 , 22 ]. Similar results have been reported from smaller cohort studies and meta-analyses and also after open ascending aortic repair [ 23 , 24 , 25 , 26 , 27 , 28 ]. Yet, quantitative PET analysis could be suggestive of perigraft gas bubbles, but no correlations with eventual bacteria and clinical outcomes of VGEI are reported [ 6 , 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, multiple [ 18 F]FDG-PET/CT scans were made in many patients, and discontinuation of antibiotic treatment was not always based on [ 18 F]FDG-PET/CT results only. A recent study in 15 patients treated with open or endovascular repair because of infected native aortic aneurysms showed that [ 18 F]FDG-PET/CT showed large discrepancies between trends of CRP and metabolic activity or even opposed course [ 20 ]. Metabolic activity in the aneurysms remained slightly elevated after the end of antibiotic treatment in patients without any signs of infection at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we enrolled as many cases as possible, referencing the prior literature. [18][19][20] The study protocol was developed and approved by the Ethics Committee of Nagoya City University Hospital (control number: 60-22-0112) before data collection and analysis. This study was also registered at umin.ac.jp (UMIN R000056536).…”
Section: Methodsmentioning
confidence: 99%